Liver Fibrosis and Mechanisms of the Protective Action of Medicinal Plants Targeting Inflammation and the Immune Response - Florent Duval; Jorge E. Moreno-Cuevas; María Teresa González-Garza; Carmen Maldonado-Bernal; Delia Elva Cruz-Vega (Hindawi Limited, 2015)
Inflammation is a central feature of liver fibrosis as suggested by its role in the activation of hepatic stellate cells leading to extracellular matrix deposition. During liver injury, inflammatory cells are recruited in the injurious site through chemokines attraction. Thus, inflammation could be a target to reduce liver fibrosis. The pandemic trend of obesity, combined with the high incidence of alcohol intake and viral hepatitis infections, highlights the urgent need to find accessible antifibrotic therapies. Medicinal plants are achieving popularity as antifibrotic agents, supported by their safety, cost-effectiveness, and versatility. The aim of this review is to describe the role of inflammation and the immune response in the pathogenesis of liver fibrosis and detail the mechanisms of inhibition of both events by medicinal plants in order to reduce liver fibrosis.